2017
DOI: 10.1002/2017gl075369
|View full text |Cite
|
Sign up to set email alerts
|

Significant Aerosol Influence on the Recent Decadal Decrease in Tropical Cyclone Activity Over the Western North Pacific

Abstract: Over the past two decades, the number of tropical cyclones (TCs) has decreased markedly in the southeastern part of the western North Pacific (WNP) as a component of the interdecadal variation. This decrease has partially been explained by an internal low‐frequency variability of sea surface temperature (SST) in the Pacific, but influences of external forcing remain unclear. Here we show that past changes in sulfate aerosol emissions contributed approximately 60% of the observed decreasing trends in TC genesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Previous studies have shown that the number of TC or typhoon genesis over the WNP has an abrupt decrease in the late season after the late 1990s, which is attributed to the La Niña-like Pacific SST change, the North Atlantic SST warming, and the external forcing such as aerosol emission (e.g., Hsu et al, 2014;Takahashi et al, 2017;Zhang et al, 2018;Zhao et al, 2019). However, there is lack of consensus on the causes for the northwestwards shift of autumn TC genesis positions over the WNP after the late 1990s.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the number of TC or typhoon genesis over the WNP has an abrupt decrease in the late season after the late 1990s, which is attributed to the La Niña-like Pacific SST change, the North Atlantic SST warming, and the external forcing such as aerosol emission (e.g., Hsu et al, 2014;Takahashi et al, 2017;Zhang et al, 2018;Zhao et al, 2019). However, there is lack of consensus on the causes for the northwestwards shift of autumn TC genesis positions over the WNP after the late 1990s.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, a few studies have paid attention to the interdecadal variation in the WNP TC during autumn or late season due to frequent catastrophic super-typhoons (e.g., Liu and Chan, 2013;Hsu et al, 2014;Choi et al, 2015;He et al, 2015;Wu et al, 2015;Hong et al, 2016;Huangfu et al, 2017;Takahashi et al, 2017;Hu et al, 2018;Zhao et al, 2019). These studies have indicated a pronounced inter-decadal change in the TC genesis number and location over the WNP during late season around the late 1990s, which is characterized by remarkable decrease in the TC number and northwestwards shift in the TC genesis position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2016) infer an anthropogenic contribution to high accumulated cyclone energy (ACE) in the western North Pacific in 2015. Exploring potential causes of recent decadalscale changes, Takahashi et al (2017) infer that changes in sulfate aerosol emissions caused more than half of the observed decline in TC frequency over the southeastern part of the western North Pacific during 1992-2011, while Zhao et al (2018) conclude that internal variability (the interdecadal Pacific oscillation) contributed to the lower TC frequency observed in the western North Pacific basin after 1998. Using a statistical analysis, Yang et al (2018) infer a contribution of global warming to record-setting TC intensity in the western North Pacific in 2015.…”
Section: Case Studies -Assessment Of De-tection and Attributionmentioning
confidence: 99%
“…Zhan et al () suggest that intense TCs formed over the western WNP have stronger coastal risk than those formed over the eastern WNP. However, despite an increase in typhoon intensity with local SST warming, the reduced developing duration (due to the northwestward shift of TC genesis location) and decreased TC frequency (e.g., He et al, ; F. Hu, Li, et al, ; Maue, ; Takahashi et al, ) tend to offset the increasing TC intensity from a typhoon destructive potential perspective (Lin & Chan, ), often with conflicting effects (Knutson et al, ). Meanwhile, there are significant westward expansions of WNP subtropical high (WNPSH) since the 1950s (Wu & Wang, ) and tropical upper tropospheric trough (TUTT) since the late‐1970s (Wang & Wu, , ; Wu et al, ), which are closely linked to the changes in steering flow and genesis location of TC, respectively.…”
Section: Introductionmentioning
confidence: 99%